Palladium-catalyzed ortho-acylation of N-Nitrosoanilines with α-oxocarboxylic acids: a convenient method to synthesize N-Nitroso ketones and indazoles. Issue 23 (8th June 2016) - Zhang, Liang; Wang, Zhe; Guo, Peiyu; Sun, Wei; Li, Ya-Min; Sun, Meng; Hua, Chengwen
Graphical abstract: Highlights: An efficient and mild protocol for regioselective synthesis of N-Nitroso aryl ketones is described. This chemistry offered a convenient access to a range of indazoles. Palladium-catalyzed decarboxylative ortho -acylation of CH bond is very important. Abstract: An efficient and mild protocol for regioselective synthesis of N-Nitroso aryl ketones by palladium-catalyzed direct acylation of arenes using N-Nitroso as directing groups is described. This reaction proceeded smoothly and could tolerate a variety of functional groups. Moreover, this chemistry offers a convenient access to a range of indazoles.